Virus-host interaction in feline immunodeficiency virus (FIV) infection - Taniwaki, Sueli Akemi; Figueiredo, Andreza Soriano; Araujo Jr., João Pessoa (Elsevier, 2013)
Feline immunodeficiency virus (FIV) infection has been the focus of several studies because this virus exhibits genetic and pathogenic characteristics that are similar to those of the human immunodeficiency virus (HIV). FIV causes acquired immunodeficiency syndrome (AIDS) in cats, nevertheless, a large fraction of infected cats remain asymptomatic throughout life despite of persistent chronic infection. This slow disease progression may be due to the presence of factors that are involved in the natural resistance to infection and the immune response that is mounted by the animals, as well as due to the adaptation of the virus to the host. Therefore, the study of virus-host interaction is essential to the understanding of the different patterns of disease course and the virus persistence in the host, and to help with the development of effective vaccines and perhaps the cure of FIV and HIV infections. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Cats; Feline immunodeficiency virus; Immune system dysfunction; Immunopathogenesis; Natural resistence